Progress and prospects of hard hexaferrites for permanent magnet applications - de Julián Fernández, C; Sangregorio, C; de la Figuera, J; Belec, B; Makovec, D; Quesada, A (Journal of physics. D, Applied physics, 2021)
Permanent magnets based on hard hexaferrite represent the largest family of magnets being used today by volume. They generate moderate remanence induction, but present crucial advantages in terms of availability, cost, resistance to demagnetization and corrosion and absence of eddy current losses. As a consequence, ferrites are the most logical candidate for substitution of rare-earths in selected applications that do not demand the best performing magnets. If the remanence of ferrite-based magnets was to be improved, even mildly, the door to a larger scale substitution could be opened. In this framework, we review here current strategies to improve the properties of hexaferrites for permanent magnet applications. We first discuss the potential of exploring the nanoscale. Second, progress related to controllably doping hexaferrites is revised. Third, results achieved by fabricating hard-soft magnetic composites using ferrites as the hard phase are presented. Finally, future prospects and new potential end applications for ferrite magnets are discussed.